Akuntabilitas dan Transparansi Catatan Dana Masjid Darul Falah Gentan Sukoharjo - Lia Kusuma Dewantari; Pardi (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2022)
The target of this research is to analize the accountability and transparency of the Darul Falah Mosque’s fund records. In the preparation of this scientific article, the merhod applied is descriptive qualitative research. Data in the form of primary data received from the mosque administrators and secondary data in the form of records of funds and information facilities used. The data collection was carried out using a triangulation technique, namely question and answer, observation, and documentation. The author analyses method according to Miles and Huberman. Data analysis revealed that the accountability carried out by the Darul Falah Gentan Sukoharjo Mosque is only based on word of mouth and was still traditional and was not stated in written rules, but the management of fund record has been approved and known by the manager. Transparency of the Darul Falah Gentan Sukoharjo Mosque fund record has been carried out by showing cash flows (deposits, withdrawals, and balances), but has not been presented on the information board provided. As a result, the records of funds managed by Darul Falah Gentan Sukoharjo are less accountable and transparent.